From Femoral to Radial Approach in Coronary Intervention: Review of the Literature and 6 Years Single-Center Experience. (April 2017) - Bianchi, Renatomaria; D'Acierno, Ludovica; Crisci, Mario; Tartaglione, Donato; Cappelli Bigazzi, Maurizio; Canonico, Mario; Albanese, Michele; Gragnano, Felice; Fimiani, Fabio; Russo, Mariagiovanna; Cirillo, Plinio; Calabrò, Paolo
Since the first cardiac catheterization in 1929, this procedure has evolved considerably. Historically performed via the transfemoral access, in the last years, the transradial access has been spreading gradually due to its many advantages. We have conducted a review of published literature concerning efficacy, safety, and cost-effectiveness, and we analyzed our patients' data, including the results of the recently published Minimizing Adverse hemorrhagic events by TRansradial access site and systemic implementation of angioX (MATRIX) study. This review confirmed the superiority of the transradial access compared to the femoral access, especially regarding complications related to the access site, duration of hospitalization, and comfort for the patient. The transradial approach is an excellent option for coronary angiography, and the procedure's risks are reduced by increased operator experience.